IMPROVEMENT OF THE MEDICAL THERAPY REGIMENS FOR PATIENTS WITH II DEGREE GENERALIZED PERIODONTITIS AT THE STAGES OF CLOSED CURETTAGE AND COMPARISON OF THEIR EFFICACY - Volosovets, T.M.; Kravchenko, A.V. (World of Medicine and Biology, 2020)
Unmotivated use of antibiotics leads to the emergence of periodontopathogenic microorganisms strains resistant to them. It is necessary to develop modern regimens of drug therapy for treatment of inflammatory and dystrophic-inflammatory periodontal tissues diseases, which would not involve the local use of antibiotics. For medical treatment of patients with generalized II degree periodontitis, two regimens of drug therapy were suggested, one of which (No. 1) included local administration of an antibiotic and a non-steroidal anti-inflammatory drug in combination with oral administration of a proteolytic enzyme (serratiopeptidase) and the second regimen (No. 2) included only non-steroidal anti-inflammatory drug in combination with oral administration of a proteolytic enzyme. The regimens efficacy was assessed by the dynamics of hygienic and periodontal indices, as well as by the quantitative index dynamics of gum fluid and the presence of histamine and serotonin in it, as the inflammatory process mediators. Patients' recovery terms were also assessed. The performed clinical studies have proved the comparability of the drug therapy regimens 1 and 2 efficacy and permitted to recommend them for implementation in dental practice.
Keywords: generalized periodontitis; closed curettage; gum fluid; histamine; serotonin